2003
DOI: 10.1002/ptr.1238
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant effects of different fractions of essential oil from Carum copticum on guinea pig tracheal chains

Abstract: In previous studies, the relaxant and anticholinergic (functional antagonism), histamine(H1) inhibitory, and xanthine-like activity effect of Carum copticum have been demonstrated on guinea pig tracheal chains. To investigate the effective component(s) of this plant, responsible for the observed bronchodilatory effect, fractionation of the essential oil from Carum copticum was carried out and the relaxant effects of different fractions were examined in this study. The bronchodilatory effect of different fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…In previous in vitro studies, reduced activity of tracheal SMC by C. carvi and C. copticum L. extracts was demonstrated (Boskabady et al, 2003;Reiter & Brandt, 1985). Recently, Gilani and his co-workers (2005) demonstrated that C. copticum extract has reduced spontaneous contractile activity and inhibited K + -induced contractions in intestinal preparation of rabbits.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In previous in vitro studies, reduced activity of tracheal SMC by C. carvi and C. copticum L. extracts was demonstrated (Boskabady et al, 2003;Reiter & Brandt, 1985). Recently, Gilani and his co-workers (2005) demonstrated that C. copticum extract has reduced spontaneous contractile activity and inhibited K + -induced contractions in intestinal preparation of rabbits.…”
Section: Discussionmentioning
confidence: 86%
“…None of these studies clearly defined the effects of caraway on gastro-intestinal motor activities, as the clinical dyspeptic syndrome is a complex pathophysiological process in which alteration of motility, alteration of sensation as well as psychosocial factors are involved in the generation of dyspepsia (Camilleri, 2001). Caraway oil inhibited the motor activities of SMC of the gallbladder, stomach, trachea and ileum (Boskabady et al, 2003;Goerg & Spilker, 2003;Micklefield et al, 2003;Reiter & Brandt, 1985). Recently, in vitro and in vivo experiments demonstrated antihypertensive, antispasmodic, bronchodilator and hepatoprotective activities for C. copticum seeds (Gilani et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is a report describing that essential oil of Carum copticum has parasympathomimetic activity and produces contraction of the smooth muscle, such as guinea pig's ileum and the bronchial musculature (Devasankaraiah et al, 1974). Recent reports indicate its relaxant activity on guinea pig's tracheal chain (Boskabadi et al, 2003) via inhibitory action on H 1 Histaminic receptors (Boskabadi and Shaikhi, 2000). Also the antitussive effect of Carum copticum is reported in guinea pigs (Boskabady et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…Each trachea was cut into 8 -10 ring shaped pieces. Each piece containing two to three cartilaginous rings, which was cut open opposite the tracheal muscle, and sutured together to form a tracheal chain (24). The tissue was suspended in a 10 mL organ bath (organ bath 61300, Bio Science Palmer-Washington, Sheerness, Kent U.K.) containing Krebs-Henseleit solution (25).…”
Section: Tissue Preparationmentioning
confidence: 99%